Designing an E-Learning Model for Health Tourism Marketing Case Study: Educational Healthcare Centers of Islamic Azad University, Tehran - Heidari , Hanieh; Doshman Ziari, Esfandiar; Barzegar, Nader; Faghiharam , Batoul; Mehdizadeh , Amir Hossein (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2024)
Objective: The present research aims to design an e-learning model for health tourism marketing in the educational healthcare centers of the Islamic Azad University in Tehran. Methodology: The research method is applied in terms of its objective and qualitative regarding its data. The population included management experts with specialized doctoral degrees, heads of educational healthcare centers of the Islamic Azad University, and their liaisons. The sampling was purposeful and snowball, selecting 14 experts until theoretical saturation was achieved. Findings: The findings indicate eight dimensions along with 47 components for the proposed model. The identified dimensions (components) include: Strategies (national and macro, regional and international), Infrastructure (scientific interactions, cultural interactions, political interactions, economic interactions, legal and ethical, research and education, management, organization, technology, support, monitoring, and coordination), Contextual Factors (political ideology, cultural ideology, economic ideology, security, and welfare facilities), Resources (financial resources, human resources, content resources, and natural tourism resources of the country), Education (clinical training, continuous education, health education, organizational education), Processes (needs assessment, design, implementation, evaluation, feedback, and corrective program), Communication Literacy Level (communication technology, intercultural communication, advertising, organizational communication, public relations, international relations, and tourist rights), and Ideation (being a pioneer, opportunity seeking, risk-taking, leveraging resources, customer orientation, value creation, and innovation). Conclusion: These results and the presented model can significantly assist in creating e-learning for health tourism marketing by the educational healthcare centers of the Islamic Azad University in Tehran. Therefore, the use of these results is recommended to the stakeholders and beneficiaries in this field.